Fiscalistic as the science of the functioning of the treasury and the management of the objects which consist the treasury - Bondarenko, Natalia L.; Konanevich, Yuri G.; Krishtal, Dmitry S.; Bondarenko, Miroslav S. (Journal of the Belarusian State University. Law, 2024)
In the system of public relations regulated by law, there is a specific group of public relations formed in connection with the functioning of the treasury and management of the objects constituting the treasury. Representatives of the scientific school of economic law of the faculty of law of the Belarusian State University founded the doctrinal foundations of fiscalistic. The present article develops this problematic, being devoted to the elaboration of the concept, disclosure of the nature, analysis of the content and formation of the system of fiscalistic as a special science of interdisciplinary nature. The authors of the article additionally argue that the institutionalisation of fiscalistic creates prerequisites for the formation of a number of independent areas of scientific knowledge, which in the future can serve as a basis for solving a number of practical problems in legal science.
Keywords: fiscalistic; treasury; fiscal regulation; fiscal law; fiscal legal relations; investment in human capital; fuel and energy complex